PERBANDINGAN WARIS ANAK LUAR KAWIN ANTARA SISTEM WARIS DI KOREA SELATAN DENGAN INDONESIA: Comparison of the Inheritance of Illegitimate Children Between the Inheritance Systems in South Korea and Indonesia - Dara Luthfia Husni; Wahyuni Retnowulandari (Reformasi Hukum Trisakti, 2025)
Inheritance issues are complex, and international marriages further complicate matters due to the pluralism of legal systems between countries. This study compares the inheritance systems for children born out of wedlock in South Korea and Indonesia. In Indonesia, inheritance is regulated by customary law, religious law (Islamic law), and the Civil Code (KUHPerdata), granting inheritance rights to children born out of wedlock based on the parents' marital status. In South Korea, the Civil Act governs inheritance for children born out of wedlock with some restrictions. The study finds that in South Korea, inheritance for children born out of wedlock is regulated by Article 855 of the Korean Civil Code, while in Indonesia, it is governed by Article 280 of the Civil Code. In case No. 2017.6.16. 2015 Gadan, the court ruled that a child born out of wedlock, proven through genetic testing, has the right to inherit the father’s property. In contrast, Decision No. 533/Pdt.G/2010/PN.MDN Jo. Decision No. 84/Pdt/2012/PT.MDN rejected the plaintiff’s claim because they were not considered a legitimate heir